2019
DOI: 10.1097/qai.0000000000001972
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Cocaine Use and Pre-exposure Prophylaxis: Adherence, Care Engagement, and Kidney Function

Abstract: Background: Concomitant use of cocaine and HIV pre-exposure prophylaxis (PrEP) raises important clinical questions around adherence, retention in care, and renal toxicity. Methods: We assessed the associations of confirmed cocaine use with PrEP adherence (both ascertained via objective measures), care engagement, and renal function in the iPrEx open label extension. Cocaine use was measured in scalp hair samples and categorized as: light (500-3,000 pg/mg) and moderate to heavy (>3,000 pg/mg). PrEP adherence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…With respect to substances, consistent with previous research (e.g., [ 42 ]), moderate/high risk cocaine use was significantly associated with PrEP nonadherence. Consuming cocaine at elevated levels may be linked to impaired neurocognitive functioning and pronounced lifestyle disruptions [ 59 ]; both of which can diminish the likelihood of following one’s PrEP regimen as prescribed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With respect to substances, consistent with previous research (e.g., [ 42 ]), moderate/high risk cocaine use was significantly associated with PrEP nonadherence. Consuming cocaine at elevated levels may be linked to impaired neurocognitive functioning and pronounced lifestyle disruptions [ 59 ]; both of which can diminish the likelihood of following one’s PrEP regimen as prescribed.…”
Section: Discussionsupporting
confidence: 89%
“…Within the context of PrEP treatment, substance use and depression on their own have been linked to PrEP nonadherence, but similar to alcohol, disparate findings have been yielded. Specifically, nonadherence has been significantly associated with the use of some types or classes of substances (e.g., stimulants, club drugs) but not others (e.g., cannabis) [36,37,[41][42][43][44]; and the presence of depressive symptomatology has been associated with both an increased and decreased likelihood of PrEP nonadherence among gbMSM [45].…”
Section: Alcohol Consumption and Adherence To Prepmentioning
confidence: 97%
“…We evaluated alcohol and SUD as clinical risk factors, as these are well-established risk factors of poor adherence and care engagement in the PrEP and HIV treatment literature. 21 , 22 , 23 Insurance type and NDI were missing in less than 0.5% of all participants and were handled using listwise deletion. Incident HIV diagnoses were identified using a KPNC HIV registry.…”
Section: Methodsmentioning
confidence: 99%
“…A single-center study based in Vancouver, Canada, found that daily crack cocaine use to adversely impact optimal pharmacy refill adherence in one prospective study [114], while another study based in Boston, MA, found heavy cocaine use to be associated with lower rates of self-reported ART adherence [115]. This finding is consistent for HIV uninfected individuals on pre-exposure prophylaxis (PrEP) as well, with lower rates of adherence among persons using cocaine or stimulants [116] [117]. Not only does cocaine use appear to decrease rates of ART adherence, multiple studies have also shown heavy use to decrease rates of viral suppression, [118] [119], highlighting the public health impact of cocaine use among PLWHA.…”
Section: Effects Of Cocaine On Art Adherencementioning
confidence: 89%